Waste and Pollution Management Practices for Green Restaurant Business in Thailand - Kachacheewa, Yotpicha; Kumsuprom, Siridech; Chomsuan, Jiraporn (Suan Dusit Graduate School Academic Journal, 2023)
Nowadays, restaurant operators were interested in environmentally friendly business or a green restaurant, which consisted of several practices. The objective of this research was to study the factors of waste and pollution practices as they clearly affected the environment. It also examined the influence of demographic factors, gender, age, and business income on these practices. The questionnaire was distributed to 407 restaurant operators in Thailand by simple sampling. The data were analyzed for these practices’ factors by Exploratory Factor Analysis (EFA) and confirmed by Confirmatory Factor Analysis (CFA). Then the factors were analyzed for relationships with demographic variables by t-test and one-way analysis of variance statistics. The results showed that in these practices, restaurant operators focus on pollution reduction, source waste reduction, waste reduction technology and waste and pollution management systems, respectively. It was also found that demographic factors, gender had no different effect on waste and pollution management practices, age and income had different effects on these partices.